Analisis Faktor yang Berhubungan dengan Fatigue pada Pegawai Dinas Kesehatan Provinsi DKI Jakarta Tahun 2022 - Halimatuzzahra, Halimatuzzahra; Erwandi, Dadan (National Journal of Occupational Health and Safety, 2022)
In 2020 cases of Covid-19 were found in various parts of the world, one of which was in Indonesia. Since it was first discovered, this case has continued to increase, with DKI Jakarta Province being the highest contributor to daily positive cases of Covid-19 in Indonesia. The Indonesian government continues to make efforts and cooperation between institutions. One of the institutions it has is the Health Agency. However, the arrangements and working conditions that have changed following the development of the Covid-19 case can cause fatigue for employees of the DKI Jakarta Health Agency.. This study aims to analyze the relationship between work-related risk factors (working hours, effort, work rewards, overcommitment, social support, and job satisfaction) and non-work-related (sleep quantity, sleep quality, health status, educational status, stress, and age) on employees of Jakarta Health Agency against fatigue. This study used a cross-sectional research design with primary data collection using a questionnaire. The results of research based on MFI found that 64 employees (45.7%) experienced general fatigue, 67 employees (47.9%) experienced physical fatigue, 67 employees (47.9%) experienced mental fatigue, 47 employees (33.6%) experienced reduced activity, and as many as 65 employees (46.4%) experienced reduced motivation with variables having a p-value